2020
DOI: 10.3389/fphar.2020.578217
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Fingerprint Analysis and Ultra-Performance Liquid Chromatography Quadrupole Time-of-Flight Mass Spectrometry-Based Metabolomics Study of the Protective Effect of Buxue Yimu Granule in Medical-Induced Incomplete Abortion Rats

Abstract: Medical abortion is a common method to terminate an early pregnancy and often causes serious complications such as abnormal uterine bleeding and endometritis. Buxue Yimu granule (BYG) is a well-known traditional Chinese medicine prescription composed of five kinds of drugs and is widely used in gynecology and obstetrics. The aim of the present study was to establish the quality standard of BYG and investigate its protective effect on incomplete abortion. The chemical fingerprint of BYG was established by high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 45 publications
1
10
0
3
Order By: Relevance
“…The chemical compositions of DXK were identified by UPLC–Q-TOF/MS according to the previous study ( Zhang et al, 2020 ). The chromatographic method was achieved adopting Acquity UPLCR BEH C18 (100 mm × 2.1 mm × 1.7 μm) as a stationary phase and 0.1% formic acid (A)/acetonitrile with 0.1% formic acid (B) as a mobile phase with gradient elution at a constant flow rate of 0.4 ml/min.…”
Section: Methodsmentioning
confidence: 99%
“…The chemical compositions of DXK were identified by UPLC–Q-TOF/MS according to the previous study ( Zhang et al, 2020 ). The chromatographic method was achieved adopting Acquity UPLCR BEH C18 (100 mm × 2.1 mm × 1.7 μm) as a stationary phase and 0.1% formic acid (A)/acetonitrile with 0.1% formic acid (B) as a mobile phase with gradient elution at a constant flow rate of 0.4 ml/min.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, stachydrine could increase uterine contraction and promote angiogenesis, which played an important role in promoting uterine recovery ( Li et al, 2013b ; Cheng et al, 2020b ). Zhang et al found that senkyunolide A, ligustilide, leonurine, and ferulic acid might jointly participate in the protection of medical-induced incomplete abortion rats ( Zhang et al, 2020 ). Our previous studies indicated that leonurine, rutin, ferulic acid, and ligustilide might be the potential components of Danggui and Yimucao regulating Th1/Th2 paradigm to relieve the immune disorders caused by medical abortion ( Bi et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies had shown that drugs could regulate metabolic disorders in amino acids metabolism and lipids metabolism, and thereby alleviating the damage caused by medical abortion. Li et al found that regulating metabolites had a certain protective effect on the uterus ( Li et al, 2019 ; Zhang et al, 2020 ). As we all know, progesterone and T helper (Th) 1/Th2 were involved in maintaining pregnancy ( Raghupathy, 2001 ), and they were also closely related to medical abortion and recurrent spontaneous abortion ( Li et al, 2013a ; Yuan et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, stachydrine could increase uterine contraction and promote angiogenesis, which played an important role in promoting uterine recovery (Li et al, 2013b;Cheng et al, 2020b). Zhang et al found that senkyunolide A, ligustilide, leonurine, and ferulic acid might jointly participate in the protection of medical-induced incomplete abortion rats (Zhang et al, 2020). Our previous studies indicated that leonurine, rutin, ferulic acid, and ligustilide might be the potential components of Danggui and Yimucao regulating Th1/Th2 paradigm to relieve the immune disorders caused by medical abortion (Bi et al, 2022).…”
Section: Discussionmentioning
confidence: 97%
“…Studies had shown that drugs could regulate metabolic disorders in amino acids metabolism and lipids metabolism, and thereby alleviating the damage caused by medical abortion. Li et al found that regulating metabolites had a certain protective effect on the uterus (Li et al, 2019;Zhang et al, 2020). As we all know, progesterone and T helper (Th) 1/ Th2 were involved in maintaining pregnancy (Raghupathy, 2001), and they were also closely related to medical abortion and recurrent spontaneous abortion (Li et al, 2013a;Yuan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%